Metode Penurunan Resistansi Pentanahan Arrester pada Gardu Distribusi untuk Meminimalisir Terjadinya Ground Potensial Rise (GPR) - Triani Mardalena Sari; Dian Eka Putra; Raden Ahmad Yani; Nofiansah (SURYA TEKNIKA, 2026)
An effective arrester earthing system at distribution substations is crucial for conducting lightning currents to prevent Ground Potential Rise (GPR). Initial measurements at PD.0431 substation showed a resistance of 6.7 Ω, exceeding the PUIL 2020 limit of 5 Ω. This study aims to reduce resistance by adding parallel rod electrodes. Measurements were taken using an Earth Tester with the potential drop method, while GPR, touch voltage, and step voltage analyses were simulated with CYMGrd (1000 A fault current). The results showed that the addition of four electrodes reduced the resistance from 6.08 Ω to 1.97 Ω, meeting the standard. Simulations showed a 52.7% reduction in GPR, a 73.9% reduction in touch voltage, and a 74.7% reduction in step voltage. The post-improvement ground potential contour was also more uniform. This study proves that the parallel electrode configuration effectively reduces resistance while mitigating GPR risks. This method is recommended for substations with similar characteristics.